CHINA’S FOREIGN POLICY IN CENTRAL ASIA AND THE BALKANS: A COMPARATIVE PERSPECTIVE - Trailović, Dragan (Political Review, 2025)
The paper analyses the foreign policy activities of the People’s Republic of China in Central Asia and the Balkans, highlighting the similarities and differences in its engagement in these geopolitically significant regions. The study adopts a comparative approach at the regional level, examining Central Asia and the Balkans as two parallel arenas of Chinese foreign policy activity. The comparative framework is structured around four dimensions: economic, political, security, and social. A comparative analysis of China’s foreign policy engagement in Central Asia and the Balkans reveals how Beijing positions itself as a global actor with a flexible and pragmatic approach that relies on economic instruments as the foundation of its influence while adapting to regional specificities. In both regions, economic engagement constitutes the dominant pillar of China’s foreign policy, primarily through the Belt and Road Initiative. Similarities are also evident in the diplomatic sphere, where China combines bilateral relations with multilateral formats, emphasizing the principles of sovereignty, mutual benefit, and non-interference in internal affairs, consistent with the concept of a “community with a shared future for mankind”. Social and cultural dimensions, such as Confucius Institutes, scholarships, and media cooperation, serve as instruments of soft power in both regions.However, despite these similarities, there are significant differences that illustrate the adaptability of China’s strategy. In Central Asia, as a neighbouring region of vital strategic importance, China demonstrates a deeper and more multidimensional engagement. This engagement is reflected in China’s economic dominance, developed trade networks, and substantial investments; politically, it relies on well-established institutional frameworks such as the Shanghai Cooperation Organization (SCO) and the China+C5 format; and in the security sphere, it is actively involved in counterterrorism efforts through security cooperation, joint exercises, and arms sales. This approach reflects the priorities of China's national security, particularly concerning Xinjiang and the Uyghur issue. Another key difference lies in the importance of energy security, as access to Central Asia's abundant energy resources represents one of China's main strategic objectives. In contrast, in the Balkans—a more distant region under stronger influence from the EU, the United States, and NATO—China's engagement is more selective and predominantly economic, focusing on infrastructure projects and access to the wider European market. Political and security involvement is limited, being most intensive in Serbia. Although China also invests in energy projects in the Balkans, such activities are primarily linked to market access and the potential securing of resources for its broader needs, rather than to immediate energy security concerns, as in the case of Central Asia. Central Asia is key to China’s security and energy needs, whereas the Balkans function as a strategic gateway to EU markets and a space for enhancing political influence on Europe’s periphery.These differences in strategic objectives and operational approaches point to the pragmatic and adaptive nature of China's foreign policy. Its actions are carefully tailored to the specific geopolitical context and characteristics of each region. In Central Asia, China acts as a co-superpower, shaping the regional order through economic, political, and security instruments, while in the Balkans, it is a secondary but rising actor seeking to expand its influence through infrastructure, loans, and political partnerships, balancing its global ambitions with the European institutional framework.
Keywords: foreign policy; Belt and Road Initiative; economic diplomacy; China; Central Asia; Balkans